Oversight and Accountability in Corrections - Michael J. Ashe Jr. (Washington University Journal of Law & Policy, 2006)
There are seven underlying principles of our vision of excellence in corrections at Hampden County: the first is balance; second is that we are in the business of not just incarceration but corrections; third is that inmates should be held accountable for being positive and productive; fourth is that whether the prison is a state prison or county facility (urban, rural or in-between) it should be part of the community; fifth is that those in custody should be kept at the lowest level of security that is consistent with public safety; sixth is that corrections should not allow itself to be a scapegoat for the failures of the larger society; and the seventh is respect.
Keywords: Prison accountability; Prison administration; Correctional institutions; United States